Activity Budgets and Forage Selection of Podolian Cattle, a Semiwild Bovine Breed. (19th May 2011) - Napolitano, Fabio; Girolami, Antonio; Pacelli, Corrado; Braghieri, Ada
Abstract : This study aimed to describe the behaviour of Podolian breed, a semiwild cattle breed kept in a natural environment (as either a small group of young bulls or cows within a family herd), and the interaction of these animals with the environment in terms of ingestion from natural pastures. Diurnal grazing behavioural pattern was monitored through continuous focal animal recording method. The activity budget of free-ranging animals was characterized by high locomotor and feeding activities. They exhibited a high degree of adaptability to the local phytocoenosis with high levels of ferns' and tree foliage intakes performed by cows and the selection of a diet more nutritious than pasture performed by young bulls. These results along with the low levels of agonistic interactions recorded in the two experiments suggest that extensive systems based on grazing allow social stability and provide a natural environment for the expression of cattle species-specific behaviour.